Future-shaping themes: Digital age foresight in Turkish university strategic plans - Oğuzhan Aytar; Rukiye Arslan (Strategic Management)
Background: Universities affect their communities and ecosystems both directly and indirectly. The strategic plans of all Turkish universities with Higher Education Council accreditation were thoroughly examined within this context. An ecosystem where digital technologies are used more efficiently and extensively is necessary for the ideal of a more sustainable environment and a world with happy people. Purpose: This study's main aim was to discover how universities in Türkiye predict the digital age via the emphasis they place on digital themes in their future plans. Study design/methodology/approach: The content analysis technique utilised within the scope of document analysis was chosen as the best method to satisfy this study's objectives. Findings/conclusions: The study found five main themes regarding the future of higher education based on codes obtained from university strategic plans. Digital transformation, digital campus, digital education, digital infrastructure, and future-focused units were these themes. We analysed the content of these five areas in connection with four types of universities around the country to see if there was a significant difference in attitude towards the digital age. Only future-focused units significantly distinguished these four types of universities, it was found. Limitations/future research: The research primarily examined the digital age themes that are evident in the strategic plans of universities. Academic studies for future research may involve an examination of the content of strategic plans in relation with different themes and categorizations. The collected results might be subjected to comparisons in order to assess the effectiveness of strategic plans.